Eugenol Exhibits Antimutagenic Activity in Model Yeast Schizosaccharomyces pombe by Regulating DNA Damage Repair System: A Transcriptomic Analysis - Muhammad Zulfiqri, Aldy; Astuti, Rika Indri; Prastya, Muhammad Eka (HAYATI Journal of Biosciences, 2025)
Free radicals that accumulate in cells can cause oxidative imbalance and trigger oxidative stress at the cellular level. Such conditions lead to damage to genetic material that accelerates cellular aging. Plant secondary metabolites have been reported to exhibit antioxidant activities that have the potential to overcome oxidative stress. Eugenol, derived from cloves (Syzygium aromaticum), has been shown to possess antioxidant activity in vitro. However, there is no information on the antioxidative activity of eugenol at the cellular level. Our study focused on the effect of eugenol as an antigenotoxic agent in preventing DNA damage caused by oxidative stress treatment. Further analysis on the cellular levels of eugenol was done through a transcriptomics study in the model yeast Schizosaccharomyces pombe. Treatment with eugenol may increase the cell viability of yeast exposed to mutagenic UV and EMS, suggesting that eugenol can act as an antigenotoxic agent. Indeed, eugenol treatment can repair DNA damage as indicated by the DNA nicking assay. Eugenol showed potential as an antiaging agent by regulating the cell cycle of S. pombe, specifically by slowing down at the G1 phase and progressing towards the S phase. Transcriptomics analysis revealed that eugenol treatment can regulate genes related to DNA damage response, specifically mismatch repair, base excision repair, and Nucleotide excision repair, in the yeast S. pombe. Our data suggest that eugenol has the potential to regulate the oxidative stress-induced DNA damage response in yeast S. pombe, which supports cell longevity.